2014
DOI: 10.1002/pssc.201300556
|View full text |Cite
|
Sign up to set email alerts
|

Is the Fermi‐level pinned on InN grown surfaces?

Abstract: In this paper, we discuss the Fermi‐level pinning issue on InN grown surfaces, in particular the nonpolar m ‐planes. Detailed angle‐resolved X‐ray photoelectron spectroscopy studies show that for intrinsic InN nanowires the Fermi‐level on the nonpolar grown surfaces is located 0.1 to 0.2 eV below the conduction band edge, i.e., not pinned in the conduction band. This indicates that the commonly measured Fermi‐level pinning in the conduction band on nonpolar grown surfaces is not an intrinsic property of InN. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Here we cleaved the samples in situ in ultra-high vacuum, leading to clean and stoichiometric surfaces. There is also one report about InN nanowire as-grown side wall facets without surface electron accumulation [19]. But all other previously used preparation techniques, requiring thermal treatments (or/and ion bombardment) rather lead to non-stoichiometric surfaces covered by In adlayers [13], also predicted theoretically to be the stable surface configuration [40].…”
Section: B Electronic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we cleaved the samples in situ in ultra-high vacuum, leading to clean and stoichiometric surfaces. There is also one report about InN nanowire as-grown side wall facets without surface electron accumulation [19]. But all other previously used preparation techniques, requiring thermal treatments (or/and ion bombardment) rather lead to non-stoichiometric surfaces covered by In adlayers [13], also predicted theoretically to be the stable surface configuration [40].…”
Section: B Electronic Propertiesmentioning
confidence: 99%
“…Hence, experiments need to be performed either at heteroepitaxially grown layers [2,7,10,[13][14][15][16][17][18] or at nanostructures [4,8,19]. However, heteroepitaxially grown layers typically contain a high density of defects, while nanostructures show interface and/or surface effects, both leading to a rather complex data interpretation.…”
Section: Introductionmentioning
confidence: 99%
“…This is attributed to Fermi-level pinning above the conduction band due to occupied surface states [7,8]. However, due to structural defects associated with the lattice mismatch to the underlying substrates, the measured surface electron accumulation in thin films and nanowires may not reflect the fundamental properties of InN [9].…”
Section: Introductionmentioning
confidence: 98%
“…The top‐left inset shows an SEM image of a nanowire probed by a tungsten tip. The right‐bottom inset illustrates the progressive shift of the Fermi‐level when increasing the bias .…”
Section: Progress Towards Intrinsic Innmentioning
confidence: 99%
“…Previously, surface electron accumulation and Fermi-level pinning had been considered as a fundamental property of InN [50,78,79]. Recent theoretical and experimental studies have suggested otherwise [80][81][82][83][84][85][86][87][88][89]. The absence of Fermilevel pinning was first measured on the cleaved nonpolar plane of InN epilayers.…”
mentioning
confidence: 99%